RANCANG BANGUN GAME EDUKASI BERBASIS MOBILE UNTUK PEMBELAJARAN SISTEM PENCERNAAN MANUSIA PADA SISWA KELAS V SEKOLAH DASAR - Fadillah wahyu ramadhan; Rara Sriartati Redjeki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning, particularly the topic of the human digestive system, still faces challenges in the form of less interactive learning media and students' difficulties in understanding abstract concepts. This study aims to design, develop, and evaluate the feasibility and effectiveness of an Android-based educational game as a learning medium for the human digestive system topic among fifth-grade elementary school students. This research employed the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The game was developed using Construct 3, featuring learning content, animation, educational mini-games, evaluation quizzes, and an automatic scoring system. Testing was conducted through expert validation by media experts, content experts, and teaching practitioners, followed by a trial involving 10 fifth-grade students using a pre-test and post-test design. The results show that the media obtained an average validation score of 3.4 out of 4 (feasible category), with an improvement in learning outcomes from an average pre-test score of 65 to a post-test score of 85 (N-Gain of 0.57, moderate category), and a student response score averaging 3.8 out of 4 (good category). This study concludes that the Android-based educational game on the human digestive system, developed using Construct 3, is feasible and effective as a science learning medium to improve elementary students' understanding and learning motivation.